Entertainment Education as a Tool for Community Empowerment and Development in Nigeria - Ugwuoke, J. C.; Nwabueze, C.; Eze, B. N.; Obetta, K. C. (Journal of Research in Adult and Continuing Education, 2025)
This paper centred on the role of entertainment education (EE) as a tool for community empowerment and development in Nigeria. The paper explored the transformative potential of EE in fostering socio-economic growth, literacy, health awareness, political participation, and cultural preservation within Nigerian communities. It traced the historical evolution of EE in Nigeria, highlighting its increasing relevance in modern educational and developmental initiatives. The study identified major challenges hampering effective EE implementation, including limited funding, cultural sensitivity issues, inadequate infrastructure, shortage of skilled professionals, political and regulatory barriers, and audience engagement difficulties among others. To address the challenges, the paper proposed strategic interventions such as promoting inclusive content creation, multimedia integration, strengthening collaborations among artists, adult education facilitators, and policymakers, embedding life skills into EE content, increasing government support, enhancing teacher training, and revising curricula. Furthermore, the paper suggested establishing community-based EE centres, integrating EE into all educational levels, encouraging localized content, setting up rural media platforms, and involving youths in programme design and implementation. It emphasized the need for supportive policies and sustained public-private partnerships to harness EE’s full potential. The paper therefore affirmed that EE is a powerful instrument for empowering individuals, promoting inclusive community development, and building a culturally vibrant, socially conscious, and economically resilient Nigerian society.
Keywords: Community Empowerment; Cultural Preservation; Entertainment Education; Entertainment Industry; Public-Private Partnerships; Socio-Economic Development